Tingkat Kepuasan Pelayanan Sales di PT. Sutan Indo Aneka Mobil Menggunakan Metode Weighted Sum Model (WSM) - Reagan Surbakti Saragih; Iwan Purnama; Dudes Manalu (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Service is one of the important things in the form of business activities engaged in the service sector. The eligibility of a person in providing the best service must go through a good assessment. Company indicators in assessing the feasibility of salesperson services at PT. Sutan Indo Aneka Mobil Pematangsiantar has many criteria. For that we need a method to be able to assist companies in making decisions. This study uses the Weighted Sum Model (WSM) method. From the calculation results of the Display Data Calculations, namely the Conformity Criteria Rating on Alternatives, Criteria Weight, WSM Calculation Method, WSM Method Calculation, the highest value is 0.925 with rank 1 meaning the Weighted Sum method. Model (WSM) helps companies in making decisions. Sales with the highest value on behalf of Putra Ade